Farmer Behavior in the Use of Pesticides on Rice Plants - Erdi Surya; Lukmanul Hakim; Liya Fitriyana; Armi; Muhammad Ridhwan; Tutiliana (Postgraduate, University of Mataram, 2024)
This study aims to determine the behavior of farmers in the use of pesticides on rice plants in Lingom Village, Indrapuri District, Aceh Besar Regency. The sample in this study was 15% of the predetermined population of 30 farmers in Lingom Village, Indrapuri District, Aceh Besar Regency who used pesticides on rice plants. Data were collected through observation, interviews and questionnaires. The results of data analysis show that farmers in Lingom Village, Indrapuri District, Aceh Besar Regency use pesticides in processing rice plants. The results showed that the behavior of farmers in the use of pesticides was in accordance with existing provisions. The pesticide used is obtained from the store, further mixed with water put in a spray tube. Pesticides that have been filled in tubes, then sprayed on rice plants. Spraying is carried out using personal protective equipment such as aprons, clothing and masks. Furthermore, farmers clean the equipment and clothes that have been used to make them clean and safe. Similarly, equipment and clothing that have been used are cleaned separately from other equipment and clothing. So as not to contaminate other family clothes during spraying, not to consume food and drinks when spraying so as not to be exposed to toxins contained in pesticides, so as not to experience injury.